1998
DOI: 10.2307/2997695
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Biodiversity and Distributional Gradients in Mangroves

Abstract: Numerous factors affect the distribution of mangrove plants. Most mangrove species are typically dispersed by water‐buoyant propagules, allowing them to take advantage of estuarine, coastal and ocean currents both to replenish existing stands and to establish new ones. The direction they travel depends on sea currents and land barriers, but the dispersal distance depends on the time that propagules remain buoyant and viable. This is expected to differ for each species. Similarly, each species will also differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
548
1
38

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 736 publications
(600 citation statements)
references
References 43 publications
13
548
1
38
Order By: Relevance
“…The growth of mangrove in four distinct zones throughout the bay and their development has presumably been controlled in the past by the time when they established themselves and environmental and biotic variables. Important environmental factors potentially controlling distribution and growth are tidal inundation, soil pore water salinity, sediment stability and type and fresh water input as discussed by several authors (Rabinowitz, 1978a,b,c;Jiménez et al, 1985;Smith, 1987a,b;Cardona and Botero, 1998;Jiménez and Sauter, 1991;Clough, 1992;Smith, 1992;Ellison and Farnsworth, 1993;Duke et al, 1998;Elster, 2000). Additionally the importance of predation on propagules and seedlings has been found to be important in establishment of mangrove.…”
Section: Discussionmentioning
confidence: 99%
“…The growth of mangrove in four distinct zones throughout the bay and their development has presumably been controlled in the past by the time when they established themselves and environmental and biotic variables. Important environmental factors potentially controlling distribution and growth are tidal inundation, soil pore water salinity, sediment stability and type and fresh water input as discussed by several authors (Rabinowitz, 1978a,b,c;Jiménez et al, 1985;Smith, 1987a,b;Cardona and Botero, 1998;Jiménez and Sauter, 1991;Clough, 1992;Smith, 1992;Ellison and Farnsworth, 1993;Duke et al, 1998;Elster, 2000). Additionally the importance of predation on propagules and seedlings has been found to be important in establishment of mangrove.…”
Section: Discussionmentioning
confidence: 99%
“…According to Duke et al (1998), coastal areas with high precipitation, high run-off of sediments, nutrients and organic matter, and high river input, such as the Amazon -which represents 16% of the freshwater discharged into the oceans (Pereira et al, 2009), tend to support higher and more diversified forest species. Rainfall and abundant river input carry muds and sands to tidal plain, forming a substrate for mangrove colonization, and also leach salts from the soil, making salinity levels constantly low and stable (Kjerfve et al, 2000).…”
Section: The Increased Rainfall Scenariomentioning
confidence: 99%
“…It was subsequently added to the mangrove flora by several authors (Table 3). However, our present study revealed the presence of Rhizophora hybrids at Havelock (South Andaman) and Kimious Bay (Car Nicobar), which stresses the importance of periodic surveys in mangrove stands where parental species of Rhizophora taxa typically co-occur (Duke 2007) as there are major taxonomic problems with Rhizophora (Duke et al 1998) despite its ubiquitous occurrence throughout the tropical world (Tomlinson 1986, Duke et al 2002. Further, it is important to note that hybrids of Rhizophora were previously reported by Ragavan et al (2011) from Havelock.…”
Section: Rhizophoraceaementioning
confidence: 53%